A direct gene transferring system for Oncidium orchids, a difficult crop for genetic transformation - Niyomtham, Krittiya; Bhinija, Kisana; Huehne, Pattana S. (Agriculture and Natural Resources, 2018)
Oncidium orchids are susceptible to damage through viral infection caused by the Cymbidium mosaic virus (CymMV). Generating a virus-resistant plant is a major challenge. Unfortunately, gene transformation in Oncidium orchids is not easy. This study developed selection steps for a direct gene transferring system through particle bombardment. Optimized hygromycin screening was reported in the transformed protocorm-like bodies (PLBs) of two commercial Oncidium hybrids (Onc. Gower Ramsey and Onc. Sweet Sugar) with the RNAi construction of the coat protein gene of CymMV. The transgenic Onc. Sweet Sugar PLBs were regenerated on a modified Murashige and Skoog medium containing hygromycin. The effective selection system in exterminating non-transformed PLBs and the functional transgene in the transgenic lines was analyzed using reverse transcription polymerase chain reaction and quantitative polymerase chain reaction. The application of this study may help the gene transformation system of other orchid plant species.